Norovirus Vaccine: Priorities for Future Research and Development - Esposito, Susanna; Principi, Nicola (Frontiers in Immunology, 2020)
Soon after its identification, norovirus (NoV) has been indicated as one of the most common causes of outbreaks of acute gastroenteritis (AGE) and sporadic acute diarrhoea episodes in subjects of any age. In 2016 the World Health Organization stated that the development of a NoV vaccine should be considered an absolute priority. Unfortunately, the development of an effective NoV vaccine has proven extremely difficult, and only in recent years, some preparations have been tested in humans in advanced clinical trials. In this paper, reasons that justify efforts to develop a NoV vaccine, difficulties encountered during NoV vaccine development, and NoV vaccine candidates will be discussed. In recent years, identification of some NoV antigens that alone or in combination with other viral antigens can induce a potentially protective immune response has led to the development of a large series of preparations that seem capable of coping with the problems related to NoV infection. Epidemiological and immunological studies have shown that multivalent vaccines, including both GI and GII NoV, are the only solution to induce sufficiently broad protection. However, even if the road to formulation of an effective and safe NoV vaccine seems to be definitively traced, many problems still need to be solved before the total burden of NoV infections can be adequately controlled. Whether currently available vaccines are able to protect against all the heterologous NoV strains and the variants of the most common serotypes that frequently emerge and cause outbreaks must be defined. Moreover, as performed clinical trials have mainly enrolled adults, it is mandatory to know whether vaccines are effective in all age groups, including younger children. Finally, we must know the immune response of immunocompromised patients and the duration of protection induced by NoV vaccines. Only when all these problems have been solved will it be possible to establish an effective immunization schedule against NoV infection and calculate whether systematic vaccination can be cost effective.